Building surface defect monitoring using photogrammetry method - Zahari N.M.; Razali S.S.M.; Aziz N.A.; Nurhikmah F.; Zawawi M.H.; Syamsir A.; Isa M.R. (American Institute of Physics Inc., 2024)
the principle of the photogrammetry techniques is the electromagnetic radiant imagery taken by drone to record, measure and interpret photographic images. This paper presents the application of photogrammetry techniques for the inspection of buildings and structures. The aim of this research is to assess the application of Unmanned Aerial Vehicle (UAV) by using drone to develop a three-dimensional mapping model, that can be used for health infrastructure monitoring. The test was conducted at College of Engineering building in Universiti Tenaga Nasional (UNITEN). The picture captured using high-resolution camera that have been attached to the drone was used and processed using Agisoft Software. The best resolution of three-dimensional mapping using Agisoft software was compared in order to identify surface defect occurs on College of Engineering buildings. As consequence, the surface defect has been found and further analysis was conducted. Findings stated that, building surface defect monitoring using photogrammetry method can be used as one of methods to conduct the building inspection and monitoring. 2023 Author(s).